2018
DOI: 10.1111/eea.12637
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crowding and host plant quality on morph determination in the soybean aphid,Aphis glycines

Abstract: Polyphenism constitutes a key example of the adaptability of a genotype to a shifting environment. In aphids, the relative production of apterous and alate individuals is influenced by cues resulting from increases in population density, changes in plant quality, and natural enemies. The ability to respond to multiple environmental cues offers aphids an effective way to optimize their fitness. Understanding the mechanisms behind alate morph production is particularly important in aphid species that are agricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 70 publications
3
21
0
Order By: Relevance
“…This strategy is considered to have contributed to the evolutionary success of aphids. Alate morph, with long wings, flight muscles and flight capability, benefits for searching hosts, escaping from natural enemies and reducing negative density-dependent population effects through dispersal (Martínez and Costamagna 2018). Nonetheless, wingless morph, with absent wings and underdeveloped flight muscles, shows an earlier onset of oviposition and higher reproductive capacity, allowing a rapid increase of the aphid colony size (Castañeda et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy is considered to have contributed to the evolutionary success of aphids. Alate morph, with long wings, flight muscles and flight capability, benefits for searching hosts, escaping from natural enemies and reducing negative density-dependent population effects through dispersal (Martínez and Costamagna 2018). Nonetheless, wingless morph, with absent wings and underdeveloped flight muscles, shows an earlier onset of oviposition and higher reproductive capacity, allowing a rapid increase of the aphid colony size (Castañeda et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In wing-dimorphic aphid species, the production of asexual alate morphs resulted from increased population density, poor plant quality and natural enemies (Braendle et al 2006). Crowding is considered to be one major environmental factor in aphids wing induction, in which the production of wing is triggered by tactile stimuli between individual aphids (Forrest 1974;Kidd and Tozer 1984;Martínez and Costamagna 2018;Purandare et al 2014). Series of signal pathways were reported to participate in the wing differentiation induced by crowding in several aphid species, including ecdysone, juvenile hormone (JH), octopamine, olfactory receptors co-receptor (Ishikawa et al 2013;Jia et al 2015;Vellichirammal et al 2017;Wang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing physical contact of pea aphids in a certain range of density caused many winged progenies (Lees, 1967;Martinez & Costamagna, 2018). Previous studies have revealed that contact between conspecific aphids or stimulation with a paintbrush induces the production of winged offspring (Johnson, 1965;Purandare, Tenhumberg, & Brisson, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal A. fabae aphids tended by the mutualistic ant Formica fusca produce a high proportion of wingless offspring, and this phenomenon might be related to a juvenile hormone-related chemical from the ants (Kleinjan & Mittler, 1975). Moreover, the high-density signaling increases the proportion of producing winged individuals in Aphis glycines, Megoura crassicauda, and A. pisum (Ishikawa, Gotoh, Abe, & Miura, 2013;Martinez & Costamagna, 2018;Wilkinson et al, 2016). Such maternal stress-induced wing dimorphism has been a research hotspot for more than a century.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, zucchini may be a better host for development of Z. cucurbitae. Rios Martinez & Costamagna (2018) investigate how crowding, host plant quality, and within-plant distribution affect morph determination in the soybean aphid, Aphis glycines Matsumura (Hemiptera: Aphididae). The authors experimentally altered density levels in the field and observed strong effects on adult body size which was used as an estimate of aphid performance.…”
mentioning
confidence: 99%